PROBLEMS OF NATIONAL (POLITICAL) IDENTITY IN THE CONTEXT OF IDEOLOGICAL DISCUSSIONS IN THE RUSSIAN POST-OCTOBER EMIGRATION - N. Omelchenko (Вестник университета, 2019)
The author’s interpretation of the content and essence of ideological and political discussions in the Russian post-October emigration in years 1920-1930 about the causes of the revolutionary collapse of Russia, the ways and prospects of the revival of the national Russian statehood has been presented. The connection between the ideological search for Russian emigration and the central for Russian social thought, the problem of understanding the originality of the Russian political process, the features of the formation and evolution of national political identity, has been substantiated. The reasons for the widespread anti-democratic views and beliefs in the emigrant environment, the growing distrust of Western democracy and liberal institutions and values have been revealed. An analysis of the political projects and models of the future revived Russia proposed by Russian emigrants («social Christianity», a renewed monarchy), which affirmed the special path of development of Russia that distinguished its «philistine» West, – has been given. The conclusion about the importance of these projects of the ideal structure of the future of Russia for the modern state development of Russia, the search for its new identity, has been made.